The impact of COVID-19 on the mental health of Lebanese pharmacists: A national cross-sectional study - Safwan, Jihan; Halat, Dalal Hammoudi; Akel, Marwan; Younes, Samar; Rahal, Mohamad; Mourad, Nisreen; Akiki, Zeina; Cherfane, Michelle; Saade, Faraj; Bouraad, Etwal; Dabbous, Mariam; Sakr, Fouad (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic has induced a global mental health crisis with variable consequences. This study aimed to assess the psychological impact of COVID-19 regarding anxiety, insomnia, depression, and response to trauma on pharmacists in Lebanon during COVID-19, and to identify factors contributing to psychological distress. Methods This was a cross-sectional study among pharmacists that involved the use of the 7-item Generalized Anxiety Disorder (GAD-7), 7-item Insomnia Severity Index (ISI), Patient Health Questionnaire 9-item depression module (PHQ-9), and Impact of Event Scale revised (IES-R) subscales. Descriptive statistical analyses were performed to determine the study distribution. The associations between the scores and the participants’ characteristics were assessed using the Chi-square test. Four binary logistic regression models were used to evaluate the association between the scores and the potential confounders, followed by four multivariable logistic regressions. An alpha of 0.05 was used to determine statistical significance. Results Participants comprised 311 pharmacists from all Lebanese districts, of whom 251 (80.7%) were females and 181 (58.2%) aged between 26 and 35 years. The majority of the participants were community pharmacists (n = 178, 57.2%). A considerable proportion of participants had symptoms of anxiety (n = 128, 41.2%), insomnia (n = 64, 20.6%), depression (n = 157, 50.5%), and subjective stress (n = 227, 78.8%). Higher anxiety (aOR: 1.73, 95% CI: 1.08; 2.78, p-value: 0.02), higher depression (aOR: 3.06, 95% CI: 1.73; 5.39, p-value: 0.001), and higher stress (aOR: 1.86, 95 percent CI: 1.11; 3.14, p-value: 0.02) scores were significantly associated with pharmacists who reported that their work involves contact with infected/suspected COVID-19 patients. Interestingly, pharmacists who expressed concern about contracting COVID-19 infection had significantly higher anxiety (aOR: 2.35, 95% CI: 1.40; 3.94, p-value: 0.001) and higher depression scores (aOR: 2.64, 95% CI: 1.49; 4.67, p-value: 0.001) respectively. Conclusion The preliminary results from pharmacists in Lebanon reflect increase in stress, burden, and frustration felt by pharmacists, creating a negative impact on their mental health and well-being during the global pandemic. As frontline healthcare workers, the role of pharmacists in the community should not be overlooked, and their mental health should be well investigated.